Mitophagy–pyroptosis–macrophage polarization crosstalk in cardiovascular diseases: mechanistic insights and therapeutic potential - Jieying Yuan; Tingru Ji; Ruquan Chen; Yuesong Yuan; Lin Ji (Frontiers in Cardiovascular Medicine, 2026)
Cardiovascular disease (CVD) is one of the leading causes of global morbidity and mortality. Its development and progression are closely associated with mitochondrial dysfunction, sterile inflammation, and immunometabolic dysregulation. Mitophagy, a key mechanism of mitochondrial quality control, maintains mitochondrial homeostasis by selectively removing damaged mitochondria. However, either insufficient or excessive mitophagy may disrupt cellular metabolism, promote ROS production and mitochondrial DNA (mtDNA) release, and activate inflammatory signaling pathways, thereby aggravating cardiovascular injury. Increasing evidence indicates that mitophagy is closely linked to pyroptosis and macrophage polarization. Impaired mitophagy can enhance inflammasome activation and gasdermin-mediated pyroptosis. In turn, inflammatory mediators released during pyroptosis may further impair mitochondrial quality control, forming a self-amplifying inflammatory loop. Meanwhile, mitophagy regulates macrophage metabolic reprogramming and phenotypic switching, thereby influencing the balance between pro-inflammatory M1-like responses and reparative M2-like functions. This review summarizes the molecular mechanisms underlying the crosstalk among mitophagy, pyroptosis, and macrophage polarization in CVD, with particular emphasis on myocardial infarction (MI) and myocardial ischemia-reperfusion injury. Current evidence suggests that restoring appropriate mitophagic flux, inhibiting aberrant pyroptosis, and reshaping macrophage phenotypes may help alleviate inflammatory injury and adverse cardiac remodeling. This review aims to provide a mechanistic framework for immunometabolic regulation in CVD and to support the development of precision therapeutic strategies targeting mitochondrial quality control and inflammatory cell responses.